The Green Betel Leaves for Inhibiting Fat Oxidation of Smoked Seasoned Catfish Fillets - Wulandari, Dwi Retno; Ekantari, Nurfitri; Husni, Amir (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
The aim of this study was to determine the effect of added betel leaves towards fat oxidation on smoked seasoned catfish fillets during storage. This study consisted of seven treatments, there were control (without added of spices, liquid smoke, and betel leaves powder), the added spices, liquid smoke, and also the combination of added spices, liquid smoke, betel leaves powder at various concentration of betel leaves powder (0.05, 1, 5, and 10%). The spices and soy sauce were dissolved in water and used to dissolve betel leaves powder. The order of smoked seasoned catfish fillets were soaked in a spice solution and betel leaves powder for 2 hours and then drained for 5 hours at 5 Â°C, and dipped in liquid smoke 10% (v/v) for 1 minute, then cooked in oven at 75 Â°C for 6 hours, cooled and packed (0.8 mm polypropylene plastic). The result showed that the betel leaves powder and spices interacted synergistically to inhibit fat oxidation and increased shelf life of smoked seasoned catfish fillets until the six days of storage. Added betel leaves powder could inhibit fat oxidation, peroxide value content varied 12.16 to 14.14 mgeq/1000 g, lower than control (13.53 to 14.09 mgeq/1000 g). Added 1% betel leaves powder was the most preferred smoked seasoned catfish fillets by consumers test, however it induced darker color, harder texture, and could covered up the smell of smoked on product. Keywords: shelf life, betel leaves, smoked seasoned catfish fillets, oxidation